ln(3x-4)=2

Simple and best practice solution for ln(3x-4)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(3x-4)=2 equation:


Simplifying
ln(3x + -4) = 2

Reorder the terms:
ln(-4 + 3x) = 2
(-4 * ln + 3x * ln) = 2
(-4ln + 3lnx) = 2

Solving
-4ln + 3lnx = 2

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Reorder the terms:
-2 + -4ln + 3lnx = 2 + -2

Combine like terms: 2 + -2 = 0
-2 + -4ln + 3lnx = 0

The solution to this equation could not be determined.

See similar equations:

| x-4/15=0 | | -2v=-20 | | 16/7+x=19/7 | | B-44=38 | | 8/x=22/(x-3) | | x/2-1/3=x/3-1/3 | | 6x+6+x=2+4x-5 | | -5r-4r+17r=73 | | 1/18+x=11/6 | | [A(w)]p=2(L+W) | | 2/(x+3)+(3/8)=5/(4x+12) | | 26=x+8 | | 13+3x+166=180 | | 8x-x=28 | | 2s-8=-7+3s | | 3(w+2)-2(w-1)+5= | | 8x-x=28 | | 2s-8=-7+3s | | 10x^2-20x=30 | | x-6/11=6/11 | | x-6/11=6/11 | | 7(t-5)+8t=5(3t+5)-9 | | 6m-23=-23+5m | | T^2+8x-8=0 | | 5(2-4d)-6d=8d-126 | | -(6y+4)-(5y-8)=1 | | 2(3+3x)-3=21 | | 56-9x=-x-64 | | s(t)=-16t^2+48t+64 | | -3(3x+4)+5x+1=25 | | 2r-2=38+7r | | -3(3x+4)+5x+2=25 |

Equations solver categories